AN UNUSUAL CASE OF MULTI-RECURRENT HERPES ZOSTER (HZ): A CASE REPORT - Bostikova, Vanda; Salavec, Miloslav; Smetana, Jan; Chlibek, Roman; Kosina, Pavel; Prasil, Petr; Plisek, Stanislav; Splino, Miroslav; Bostik, Pavel (Biomedical papers, 2011)
Aims: We report a case of multi-recurrent herpes zoster in a 53-year-old Caucasian woman treated repeatedly at the Faculty Hospital Hradec Kralove, Czech Republic over the years 2009 - 2011. Methods: Specific PCR methods targeting single nucleotide polymorphisms (SNPs) in open reading frames (ORF) 38, 54 and 62 were utilized to determine vaccine or wild type varicella-zoster (VZV) strains followed by SNPs analysis using two amplicons in ORF 22 and/or ORF 21/ORF 50. Additional genotyping in ORF 1, 6, 9 and 28 was subsequently performed due to the unusual results. Results: Three sets of clinical specimens from one patient (from hospital visits 2, 3 and 4) were analyzed and the presence of an unusual wild-type strain of VZV was discovered. The VZV strain isolated from the lesions bears a combination of markers characteristic both for Mosaic 2 (M2) and European 1 (E1) wild-type VZV strains. Conclusion: This is the first report of atypical wild-type VZV strain circulating currently in Czech Republic.
Keywords: Herpes zoster/Varicella-zoster virus/Wild-type strain/Czech Republic